NILAI STRATEGIS KURIKULUM PENDIDIKAN BAHASA INGGRIS-BERBASIS KKNI FKIP UNIVERSITAS ISLAM BALITAR - Teguh Budiharso (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2016)
This study describes English Language Education Curriculum (ELEC) of Balitar Islamic University delineating needs analysis, tracer study and action plan that is devised considerably upon National Qualification Framework. The study used content analysis implementing qualitative approach. Data were collected from curriculum document, strategic plan of UNISBA, workshop, and Focus Group Discussion conducted at UNISBA for two-month visit. The study revealed that (1) ELEC has been organized in adherence to KKNI containing 144 credits, (2) semesterly course distribution is outlined into: 20 credits each in the first and second semester, 22 credits each in the third up to sixth semester, and 16 credits in seventh semester, (3) diploma supplement as subsequent competency is programmed in terms of workshop in academic literacy, TEFL, enterpreheneurship, IT and computer, and academic writing, (4) competency elements are categorized into: personality development (KPK), work skill (KKK), expertise and knowledge (KKP), methods and knowledge degree (KMK), and managerial skills (KKM) imposed by KKNI.